Ustawa 2.0 w prakseologicznym projekcie ustanawianej rzeczywistości - Dembiński, Mariusz (Studia Edukacyjne, 2020)
The 2.0 law has come into force. However, its effects will be determined by the methods of its implementation by the staff of the Ministry of Science and Higher Education, the authorities of Higher Education Institutions in Poland and academics dealing with science and arts. Achieving a consensus that satisfies all parties requires cooperation, openness to others, as well as work on the development of cooperation itself. The aim of the article is to emphasize the development of cooperation, which, according to the author, should be conditioned by “research in action”. Therefore, drawing attention to the elements of this structure, taking into account the “historical consciousness”, embedding these activities in the phronesis and developing the forms of understanding included in it, should be the foundations of an interpretation of the 2.0 law. However, the interpretation of this law will prove more friendly (useful) for the interested parties themselves, if the research in action will take into account the general idea of praxis.